Mistaken identities - Quinn, Tara Taylor (Quinn, Tara Taylor. Sierra's web., 2025)
Bodyguard Isaac Forrester knows Savannah Compton is desperate to find her long-lost, kidnapped sister, but he refuses to let her put herself at risk. Stepping in to keep her safe, he soon learns her deepest secret--she's been in witness protection since she was seven years old. When their reluctant partnership blossoms into something more intimate, Isaac's own undercover FBI operation is revealed. The revelations could compromise their hearts, their futures and their lives.